Efektifitas Pendekatan Saintifik dalam pembelajaran IPA Untuk Meningkatkan Hasil Belajar Siswa Tunagrahita di Home Schooling Primagama Malang - Nuzulia, Nuril (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
The scientific approach is a learning process designed to enable students to learn actively by doing the 5 M process of observing, asking, trying, reasoning and communicating. Learning by using a scientific approach can encourage students to find out from various sources by making observations and not just receiving knowledge from teachers. The purpose of this research is to know the effectiveness of the scientific approach in improving the learning outcomes of the 4th grade students in natural science learning materials of various forms of leaf bone, stems, and roots in Home Schooling Primagama Malang and SLB Tarik Sidoarjo. This research uses a quantitative approach with a simple experimental research type. Method in the form of observation, interviews, questionnaires and documentation. From the 4th grade of Home Schooling Primagama Malang and SLB Tarik Sidoarjo, 2 classes were taken: the experimental class (Home Schooling Primagama Malang) and the control class (SLB Tarik Sidoarjo) with 5 students Home Schooling Primagama Malang and 7 students of SLB Tarik Sidoarjo. Analysis used Independent t test with SPSS 16 tool. From the research result can know the average value of learning result of experiment class 91, mean while control class average learning result 78 and Sig 0,001 0,05 then Ho rejected, its mean that there is a difference in learning outcomes from the experimental class with the control class. So it can be concluded that the very effective approach can improve the learning of natural science with the material of various forms of leaf bone, stems, and roots in Home Schooling Primagama MalangScientific approach; learning outcomes; Natural Science